Catalytic effects of alkali carbonates on coal char gasification. Issue 4 (August 2017) - Ding, Lu; Dai, Zhenghua; Wei, Juntao; Zhou, Zhijie; Yu, Guangsuo
Abstract: In this work, effects of K2 CO3 and Na2 CO3 additives on catalytic gasification of Shenfu coal were studied by the combination of thermogravimetric analyzer (TGA) and an in-situ heating stage microscope. Effects of loading amounts of catalysts (2.2 wt.%, 4.4 wt.%, and 6.6 wt.%) and gasification temperatures (700–950 °C) on the interactions during the char–ash/slag transition were analyzed. The results show that the interactions of catalysts with coal at gasification phase varied with reaction temperature, and compared to K-form char, Na-form char showed a more significant melt and flow of catalysts when the temperature was higher than the melting point of catalyst. The different aggregation states of catalysts on the surface of char matrix and development degrees of pore structure of char matrix accounted for the differences in interaction forms of K catalyst and Na catalyst with coal char. The interaction mechanisms of catalysts with char matrix during char–ash/slag transition were proposed and were related to the variation of gasification reactivity of char with increasing reaction temperature. Moreover, the ratio of the initial reaction rate of char loading catalyst to that of raw coal char (the specific reactivity) and the optimal loading amount of catalysts were analyzed considering the optimal gasification efficiency. There is a threshold value of reaction temperature lower than the melting point of catalyst for the optimal gasification efficiency during the gasification processes of Na-form and K-form chars. Highlights: Interactions of alkali carbonates with coal are observed by heating stage microscope. K and Na catalysts present different reaction forms with the dosage of 2.2–6.6 wt.%. A threshold temperature is observed for the optimal gasification efficiency.